Les misérables - Sundel, Alfred (Classics illustrated (Newbury (England)), 2019)
Presents a graphic novel retelling the story of a man who while trying to forget his past and live an honest life risks his freedom to take care of a motherless young girl during a period of political unrest in Paris.